PERHUTANAN SOSIAL SEBAGAI INSTRUMEN PENINGKATAN EKONOMI LOKAL: TELAAH IMPLEMENTASI DI KABUPATEN MAMASA - Verawati; Obed Bida; Nani Harlinda Nurdin (Journal Publicuho, 2025)
This study aims to analyse the implementation of the Social Forestry Policy in improving the income of forest-dependent communities in Mamasa Regency, West Sulawesi Province. The program is designed as an affirmative policy to address inequitable access to forest resources and promote community welfare through forest-based entrepreneurship. Using a descriptive qualitative approach with a case study method, the research applies George C. Edward III’s policy implementation model, focusing on four variables: communication, resources, disposition, and bureaucratic structure. Findings show that communication between implementers and target groups is effective; human resources are competent; however, financial limitations remain a major constraint. Implementers demonstrate strong commitment and integrity, and the bureaucratic structure operates by simple and clear SOPs. Income increases were observed only among active groups that received operational support. Key obstacles include insufficient funding and lack of production facilities, while supporting factors consist of effective coordination, implementer commitment, and organisational clarity. The results highlight the critical role of actor synergy, sustainable funding, and local initiative in policy success. Therefore, strengthening collaboration, ensuring equitable financial support, and building group capacity are essential to ensure long-term sustainability of the program in enhancing forest community livelihoods.